COMPARATIVE STUDY OF THE EFFECT OF SUPEROXIDE SOLUTION VERSUS CHLORHEXIDINE GLUCONATE SOLUTION IN SURGICAL WOUND DRESSING - WALIA, BHUPINDER SINGH; DUGG, PANKAJ; PALIWAL, KESHAV; SHARMA, SANJEEV; KUMAR, ASHWANI (Asian Journal of Pharmaceutical and Clinical Research, 2022)
Objective: The objective of the study is to compare the effect of superoxide solution (SOD) and chlorhexidine gluconate on wound healing. Methods: Hundred patients with different types of wounds were recruited in this study and randomized to two groups: Group A- SOD group and Group B- Chlorhexidine group. Observations were made regarding type of wounds, reduction of edema, culture of wounds, improvement, cure rates, and hospital stay. Results: Although there were no significant difference in the reduction of edema and swelling of wound in both groups, the cure rates were statistically better with SOD (p=0.001) and hospital stay was also less with the use of SOD (p=0.006). Conclusion: SOD treated case showed less morbidity, with more improvement, and more cure rate compared to chlorhexidine solution with statistically significant p-value. However, further research into the use of SOD and the cytotoxic nature of chlorhexidine in the treatment of various wounds is required.